Contribution of Self Control and Peer Conformity to Consumptive Behavior - Amal Hayati; A. Muri Yusuf; Megaiswari Biran Asnah (Universitas Negeri Padang, 2020)
The occurrence of consumptive behavior among adolescents is caused by several internal factors such as self-control, talents, interests, values, self-concepts and knowledge and learning outcomes. External factors such as social class, family, culture, peers, and situations. Psychological factors such as information processing and learning.This study aims to describe the contribution of self-control and peer conformity to the consumptive behavior of students in Kisaran Private IT High Schools. The research method uses a quantitative approach with descriptive correlational type and multiple regression. The population of this study was 57 high school IT private high school students in class X and the sample of 50 students were selected using proportional random sampling. The research findings show that: (1) on average, self-control is in the very high category, (2) peer conformity is also in the very high category, (3) consumer consumptive behavior is categorized very well, (4) there are 51% contribution of self-control to consumptive behavior, (5) there are 34% contribution of peer conformity to consumptive behavior, and (6) there are 60% contribution together with self-control and peer conformity towards consumptive behavior.